2010
DOI: 10.1016/j.vetpar.2009.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired visceral leishmaniasis in non-human primates in Brazil

Abstract: Visceral leishmaniasis (VL) is a chronic and often fatal protozoal disease that is endemic in Belo Horizonte (State of Minas Gerais, Brazil). Leishmania sp. is an intracellular obligatory parasite of macrophages that can naturally infect several mammalian species. Non-human primates (NHP) have been used as experimental models for infection with Leishmania of the donovani complex. The present report describes a case of visceral leishmaniasis in a black-fronted titi. Among 41 primates kept in captivity in a zoo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Leishmania sp. has been previously detected by PCR in the peripheral blood of this species (Malta et al 2010). Anti-L. mexicana IgG antibodies have been detected in two species of the Alouatta genus, i.e.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Leishmania sp. has been previously detected by PCR in the peripheral blood of this species (Malta et al 2010). Anti-L. mexicana IgG antibodies have been detected in two species of the Alouatta genus, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The diagnosis was confirmed by IFAT, PCR and direct observation of amastigotes in macrophages from liver, spleen, lymph nodes and skin . Malta et al (2010) reported a case of confirmed clinical leishmaniasis in a black-fronted titi monkey (Callicebus nigrifrons) also from ZBF-BH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, leishmaniasis has been described in a number of neotropical primate species kept in a zoological setting in Brazil and an immunohistochemistry technique used to identify amastigotes in macrophages of the liver and intestine. 48 …”
Section: Protozoan Localizationmentioning
confidence: 99%